Marie-Helene Bourcier: Queer Zones 3. Identites, cultures et politiques.(Book review) - Baril, Alexandre (Recherches Feministes, 2012)
Compte-rendu du livre Queer Zones 3. Identites, cultures et politiques de Sam Bourcier.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; arts; cours; discipline; europe; france; identités LGBTQIA2+; lit4700; premier cycle; périodes historiques; queer; ressource en ligne; régions géographiques; sciences humaines; sexualité; sociologie; thématiques; études culturelles; études littéraires

Elles eurent beaucoup d'enfants– et se marièrent histoire d'une famille homoparentale - Blanc, Myriam (Bec en l'air, 2012)
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; discipline; europe; filiation; france; hétérosexisme; identités LGBTQIA2+; mariage; maternité; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

How they got it and how they wanted it: Marginalised young people's perspective on their experiences of sexual health education - Brown, Graham; Sorenson, Anne; Hildebrand, Janina (Sex Education, 2012)
Young people in Australia are at greatest risk of contracting sexually transmitted infections, and priority actions are necessary for this population group. This study of marginalised and at-risk young people in out-of-school environments was conducted in Western Australia with the aim of obtaining young people's perceptions about their experience of sexual health education and preferred means of gaining sexual health knowledge and skills. A participatory research methodology was implemented through a series of workshops with 88 young people recruited through community youth agencies. The results of the study support what is already known about sexual health promotion for young people and the importance of a holistic approach to promoting positive relationships and sexual health. However, the findings emphasise that this should include the need for demonstrated trust, confidence and safe environments, and the complementary role of community youth agencies and peer-based programmes which may play an important role in reaching young people who may disengage with, or not be reached by school-based sexual health education.
Keywords: 2000 à aujourd'hui; 2000-2009; adolescentes*; australie; discipline; personnes marginalisées; périodes historiques; recherche participative; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; thématiques; éducation sexuelle

Réflexions sur la question gay - Eribon, Didier (Flammarion, 2012)
L'irruption sur la scène publique, culturelle et politique de l'affirmation homosexuelle a entraîné, au cours des dernières années et à l'échelle internationale, une prolifération de discours sur la définition même de l'homosexualité, et soulevé tout un ensemble de problèmes théoriques, sociologiques, philosophiques : Qu'est-ce qu'un homosexuel aujourd'hui ? Qu'est-ce qu'une identité ? Qu'est-ce qu'une mobilisation politique ? Comment les gays peuvent-ils reformuler eux-mêmes leurs propres personnalités, dans un geste toujours recommencé d'écart par rapport aux normes ?
Section: 615 p. ; 18 cm.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; europe; france; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

Plaisirs croisés: gukuna-kunyaza. Missions, corps et sexualités dans le Rwanda contemporain - Michela Fusaschi (Genre, Sexualité et Société, 2012)
Based on ethnographic research in post-genocide Rwanda, this article analyzes how femininity is embodied through a ritual practice called gukuna, which consists of the elongation of the labia minora through a reciprocal massage between young women. This social construction of the female body, in addition to kunyaza, a traditional male sexual technique, is expected to facilitate pleasure during sexual intercourse. Through an analysis of colonial period texts as well as recent interviews, this article shows how this ritual, has persisted in the country despite its condemnation by the Catholic Church since the colonial time, and explores how it is being reinterpreted by women.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; afro-féminisme; approches et analyses; corps; cours; discipline; féminisme africain; gukuna; premier cycle; périodes historiques; rituel; rwanda; régions géographiques; science politique; science politique et droit; sex2283; sexualité; thématiques

La notion d'homophobie, ses usages et son rapport au féminisme - Perrin C.; Roca I Escoda M.; Parini L. (Nouvelles Questions Feministes, 2012)
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; discipline; homophobie; homosexualité; hétérosexisme; identités LGBTQIA2+; lesbianisme; phi2030; philosophie; premier cycle; périodes historiques; queer; sciences humaines; sexualité; systèmes d'oppressions; thématiques